Pelatihan Penggunaan Aplikasi Duolinggo dan Hellotalk sebagai Media Pembelajaran Bahasa Inggris di SMA Leona Desa Lotas di Daerah Terpencil di Perbatasan NKRI-RDTL - Oktaviana M.F.Q. Bobe; Rozario Mendonca da Costa; Yustina Sako; Agustinus Seran; Adrianus Berek (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
The development of mobile technology provides new opportunities for independent English learning through digital applications. This community service research aims to implement training on the use of Duolingo and HelloTalk English applications at Leona High School, Lotas Village, Rinhat District. The training was conducted in two weeks, combining lecture methods, demonstrations, direct practice, group discussions, and evaluation through pre-tests and post-tests. The results showed an increase in the average score from 55 to 78 (p < 0.001), with 72% of participants consistently studying daily during the training. In addition to improving basic English skills (vocabulary, reading comprehension, and sentence structure), the training also succeeded in building independent learning habits and digital literacy. Obstacles emerged, especially internet access and limited premium features on some applications. Advanced programs (advanced grammar & speaking), mentoring, and provision of digital infrastructure support are recommended